2018
DOI: 10.4025/actascianimsci.v41i1.42553
|View full text |Cite
|
Sign up to set email alerts
|

Maniçoba hay or silage replaces Tifton 85 hay in spineless cactus diets for sheep

Abstract: The aim of this study was to evaluate the replacement of Tifton 85 hay (Cynodon spp.) by maniçoba hay or silage (Manihot glaziovii Muell. Arg) on sheep intake and performance. Twenty-four male Santa Ines animals were used, with initial body weight of 19.77 ± 1.95 kg and average age of 160 days. The animals were distributed in three treatments (Tifton 85 hay-TH, Maniçoba hay-MH and Maniçoba silage-MS), arranged in a randomized blocks design, with 8 replicates per treatment. The feedlot period lasted for 71 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…The response from the use of maniçoba hay in relation to Tifton 85 hay as a source of roughage for the intake variable was expected and is probably related to the high nutritional value of the forage, with adequate CP content and high digestibility of non-fibrous carbohydrate (Maciel et al, 2019). According to França et al (2010), the maniçoba presents anatomical characteristics similar to those of C3 plants, so that its anatomy favors the intake and, consequently, the digestibility, due to the arrangement of the mesophyll with more intercellular spaces than in C4 plants, as well as more spaces between the vascular bundles, which may have conferred to the maniçoba hay greater ruminal degradation when compared to Tifton 85 hay.…”
Section: Resultsmentioning
confidence: 94%
“…The response from the use of maniçoba hay in relation to Tifton 85 hay as a source of roughage for the intake variable was expected and is probably related to the high nutritional value of the forage, with adequate CP content and high digestibility of non-fibrous carbohydrate (Maciel et al, 2019). According to França et al (2010), the maniçoba presents anatomical characteristics similar to those of C3 plants, so that its anatomy favors the intake and, consequently, the digestibility, due to the arrangement of the mesophyll with more intercellular spaces than in C4 plants, as well as more spaces between the vascular bundles, which may have conferred to the maniçoba hay greater ruminal degradation when compared to Tifton 85 hay.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, maniçoba ( Manihot pseudoglaziovii ) represents a complementary alternative to the nutritional deficit present in cactus pear, due to its high nutritional value, contributing to significant increases in the contents of DM, NDF and crude protein (CP). It is a native species adapted to semiarid conditions and, therefore, easy to obtain, which ensures the feeding of the herd during the most critical time of the year (Gouveia et al ., 2015; Maciel et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Maniçoba hay is richer in ADF (462.7 g kg -1 vs 386.2 g kg -1 ), NFC (124 g kg -1 vs 25 g kg -1 ) and EE (18.7 g kg -1 vs 11.3 g kg -1 ) than Tifton hay; therefore, the fractions of ADF, NFC and EE in the experimental diets increased with increasing levels of maniçoba hay. Maciel et al (2019) also observed a higher intake of NFC and EE in sheep fed with maniçoba hay than those fed Tifton hay 85.…”
Section: Resultsmentioning
confidence: 63%